Thriving in crisis : Buddhism and political disruption in China, 1522-1620 - Zhang, Dewei (Sheng Yen series in Chinese Buddhist studies., 2020)
"Scholars of Chinese Buddhism long disparaged late-imperial Buddhism, and Ming-era Buddhism in particular, as degenerate, part of a decline from the glories of the Sui-Tang Buddhism of sixth through the tenth centuries CE. In recent decades, scholars have challenged this narrative of decline and degeneration, but their alternate conception of the history of Buddhism in China as one of alternating periods of decline and renewal has tended to focus on the doctrinal or theoretical contributions of individual masters, leaving open the questions of what, practically speaking, a Buddhist renewal is and how one comes to happen. In Thriving in Crisis, Dewei Zhang comes to grips with the idea of Buddhist renewal through a systematic study of the late Ming Buddhist renewal from a religio-political perspective. Zhang explores the history of the boom in enthusiasm for Buddhism in the Jiajing-Wanli era (1522-1620) and reveals the social and political factors that both caused and were caused by the Ming-era renewal. In doing so, he provides a new theoretical framework for the decline/renewal conception of Buddhist history in China"--